Self‐Assembled Asperities for Pressure‐Tunable Adhesion (Adv. Mater. 5/2023). Issue 5 (2nd February 2023) - Deneke, Naomi; Booth, Jamie A.; Chan, Edwin P.; Davis, Chelsea S.
Abstract : Pressure‐Tunable Adhesives In article number 2207337, Chelsea Davis and co‐workers show that pressure‐tunable adhesives (PTAs) demonstrate variable adhesive separation forces depending on the application pressure used to form the interface. PTAs are formed by annealing a polymer film on a silicone surface so that it dewets, forming polygonal clusters. The large gray circle is the flat face of a cylindrical probe about to make contact with the PTA during a probe‐tack adhesion experiment.